The Slow Learner: Feeling our way to Thinking about Lifelong Learning - Barter, Derek (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
This article is a critique of the current formal education system as a construct for consumerism, where the value of learning is geared towards increasingly limited instrumentalist ends. It considers alternative ways of educating the population to prepare for a century of disruption and upheaval as we transition from an unsustainable fossil fuel-based economy, where competition and acquisition are lauded to a less frenetic, but ultimately more egalitarian reflective future. It argues against the short-term myopia of credentialism, determined by election cycle politics and competitive advantage, and instead posits a humanistic vision for community education and teaching innovation that takes the longue durée regard of the history of human relations into account.Accepting Gellner’s exo-socialisation model for mass education in the industrial age, it asks what will replace this in a post-industrial world. Beginning with the principles of widening participation and social inclusion as the starting points for a socially just education, it argues that relationships are central for emancipatory education to take effect. It uses two programmes offered by Maynooth University’s Department of Adult and Community Education, the Communiversity and the Critical Skills modules: A Social Analysis of Everyday Life, as examples of programmes that have inclusion, equality and diversity, and social justice as core principles in their modus operandi. Here participation, dialogue, reflection, and a willingness to engage offer hope for an intergenerational lifelong learning approach to education in the twenty-first century that is ‘thought led’ rather than ‘market driven’.